Two new Paleogene insect fossil localities in southern Henan Province, central China - Ni, Zi-Jie; Nel, André; Ji, Gao-Zhe; Huang, Di-Ying (Zootaxa, 2025)
Paleogene insects in China are well documented from Eocene Fushun amber. In contrast, Paleogene insects preserved in sedimentary rock are poorly recorded, although they appear to represent a potentially rich resource, as evidenced by specimens from Eocene deposits in Tibet and the Paleocene Buxin Formation in Guangdong. Here, we report two new localities in southern Henan Province, central China. Relatively abundant insect fossils have been recovered from the middle–upper Eocene Hetaoyuan Formation near Tanghe City. In addition, both insect and plant fossils have recently been collected from the middle–upper Eocene Wulidun Formation near Tongbai County. These new discoveries highlight the significant potential of Eocene insect fossil resources in China.